Pengaruh harga, promosi dan lokasi terhadap keputusan pembelian rumah KPR subsidi di PT Sinar Jaya Putra Kampar Batam - Sembiring, Elwin Frandika; Sunargo, Sunargo (Jurnal Paradigma Ekonomika, 2022)
PT Sinar Jaya Putra Kampar is one of the developer companies in Batam City. This study aimed to determine the effect of price, promotion, and location on purchasing decisions at PT Sinar Jaya Putra Kampar. The sampling technique in this study used a saturated sampling technique for as many as 114 consumers in the Oleana Park Tanjung Piayu housing project. Data were obtained by distributing questionnaires directly to respondents. The data analysis method in this study is multiple regression which includes: a validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, coefficient of determination test, T-test, and F test. The results showed that price had a positive effect. And partially significant on purchasing decisions with t count 6.781 > t table 1.658 and sig 0.000 < 0.05, the promotion has a positive and somewhat substantial influence on decisions with t count 2.998 > t table 1.658 and sig 0.003 < 0.05, location has a positive effect and partially significant on purchasing decisions with t count 7.677 > t table 1.658 and sig 0.000 < 0.05 and price, promotion and site have a positive and significant effect simultaneously on buying decisions can be seen from F-count with a value of 120.368 > F-Table 2, 68 and with a sig value of 0.000 < 0.05.